ANALISIS PRAGMATISME KEKUASAAN INTERAKSI GURU-SISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Mujianto, Gigit; Setiawan, Arif; Inderasari, Elen (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the pragmatism of power in teacher-student interaction in Indonesian language learning. The main issue raised is how the power applied in this interaction affects the teaching and learning process and how aspects of pragmatism play a role in shaping the dynamics of power. This study aims to identify the forms of power that appear in teacher-student interaction and how they affect Indonesian language learning effectiveness. The method used is qualitative research with a descriptive approach, where data is obtained through observation, interviews, and document analysis from several Indonesian classes in high schools. The collected data was analysed with a pragmatic approach to reveal the role of power in these interactions. The study results show that power in teacher-student interaction significantly affects the learning atmosphere, both positively and negatively, depending on how teachers use it in the learning process. The conclusion of this study emphasises the importance of awareness of the power dynamics that occur in learning to create a more inclusive and effective educational climate.